Dehydroxylation Reaction Kinetic Mechanism of Inderite Mineral - Piskin, Mehmet Burcin; Figen, Halit Eren (INT ASSOC COMPUTER SCIENCE & INFORMATION TECHNOLOGY PRESS-IACSIT PRESS, 2011)
Dehydroxylation kinetic of Kirka inderite mineral is investigated based on thermogravimetry analysis (TGA) and fourteen different solid-state mechanisms are applied to determine of dehydroxylation kinetic mechanism. Dehydroxylation experiments were carried out at five different heating rates of 2, 5, 10, 15 and 20 degrees C/min in pure nitrogen atmosphere to obtain the thermal curves under non-isothermal conditions. It is found that random nucleation is the most probable mechanism of dehydroxylation of inderite mineral.
Keywords: Dehydroxylation; inderite mineral; kinetic mechanism; thennogravimetry; Engineering